Brain lymphatic vessels accompanying meningeal arteries in the human - Safiye Çavdar; Damlasu Altınöz; Tevriz Dilan Demir; Acar Bayraktaroğlu; İlke Ali Gürses; Gülnihal Özcan (Elsevier, 2024)
Introduction: Recent studies showed the connection between cerebrospinal fluid (CSF) and deep cervical lymph nodes (dCLN) via lymphatic vessels (LV)s. These LVs accompany dural sinuses, cranial nerves, and arteries. The present study aimed to show in addition to the main trunk of the middle meningeal artery (MMA) whether the anterior and posterior branches of MMA; the anterior (AMA) and posterior (PMA) meningeal arteries also have a role in brain lymphatic drainage in humans. Materials and method: Samples of the middle meningeal artery (MMA) and its two main branches (anterior and posterior), anterior and posterior meningeal arteries (AMA and PMA) were obtained from 3 cadavers and 6 autopsies. Podoplanin (PDPN) (lymphatic endothelial marker) and CD31 (vascular endothelial marker) immunohistochemistry (IHC) were applied to 5 μm thick transverse sections and counterstained with hematoxylin. Furthermore, western blotting techniques were applied to the same tissue samples in 3 autopsy cases to demonstrate the presence of PDPN. Results: We observed the presence of the LVs along the main trunk of MMA and its two branches, AMA, and PMA. The LVs along the MMA (main trunk) had a larger diameter range than its branches and the AMA and PMA. The diameter of LVs of the PMA was larger than AMA. Furthermore, fluid channels with varying diameters and densities were closely localized to the LVs. The western blot PDPN protein expression confirmed IHC results. Conclusion: The LVs along the main trunk, anterior and posterior branches of the MMA, AMA, and PMA also provide an extracranial pathway for thought drainage of waste from the brain tissue in humans. Thus, the organization of the extracranial transport of LVs of the brain should be well-defined for understanding the role of lymphatic drainage in various neurological diseases.